Le geste risque-tout : Écrire - Michel Guérin (Interfaces)
Among physiological and technical gestures, writing is essentially a reversed gesture. Hence the metaphysical ambiguity attached to writing, with its mnemomorphic/hypomnemata effects – as it bypasses memory and develops as a complex system based on a risky trade-off. Writing, as Proust suggests in Time regained, entirely relinquishes the world of sensible immediacy to devote itself heroically to win it back through reconstruction – it cuts itself from the world to replace it with an analysis of it, without ever knowing whether this “catastrophic” attempt will be successful.